PERANCANGAN DETEKTOR QR _CODE SERTA PENGUKURAN JARAK SENSITIVITAS KAMERA SMART PHONE UNTUK EFISIENSI WAKTU PENYORTIRAN PRODUK. - Uminingsih _; Miftah Nur Ikhsan (PROSIDING SNAST, 2018)
To read the validity (according to the design) of a data (text or numeric) which is written on an object in large quantities is very time consuming. To ease the work, the data is made in the form of a secret code (QR-Code) which can be updated at any time by an authorized admin. Code reading can be done using QR-Reader and scanned using the camera. In order to detect the validity of the data, it is really time efficient, so the system outputs display are designed (red = data is not appropriate, green = data is appropriate, QR not found = incorrect data). By utilizing camera facilities and application programs wich are existed on smart phones, a QR code detection system can be created. In this paper, the stages of detector design, the system testing, and the measurement of smartphone camera sensitivity as a function of distance are described. The object wich is detected is the expiration date on the product packaging. The results of the data detection system wich was build show in accordance with the design. The results of measurement of smartphone camera sensitivity in reading QR codes are: for Sony smartphones (D2305 series) the minimum distance is: 4.5 cm and a maximum of 19 cm, while for Samsung (j11OG SM_ series) a minimum distance of: .4 cm and a maximum of 16 cm. The build system can help the sorting work of product more efficiently.